A comparative study on tool wear and laminate damage in drilling of carbon-fiber reinforced polymers (CFRP). (1st November 2016) - Gaugel, Simon; Sripathy, Prithvi; Haeger, Andreas; Meinhard, Dieter; Bernthaler, Timo; Lissek, Fabian; Kaufeld, Michael; Knoblauch, Volker; Schneider, Gerhard
Abstract: Preliminary to successful assembling, drilling of composites like carbon-fiber reinforced polymers (CFRP) is an important but difficult process. The anisotropic and heterogeneous structure of the laminates and the highly abrasive nature of the carbon fibers make it prone to critical damages in the workpiece as well as extensive tool wear. In this work, drill series with uncoated and diamond coated tungsten carbide hard metal tools were performed in two CFRP laminates with significant differences in their microstructure. The tool wear behavior and the corresponding workpiece damage were intensively studied to figure out the correlations between wear and delamination damage. Therefore, novel and well established methods in tool wear analysis and delamination assessment based on light optical microscopy were applied and critically evaluated. The abrasive tool wear on uncoated carbide drill can be well described by the cutting edge rounding (CER) allowing strong correlations with the inflicted workpiece damage, whereas for coated tools measuring CER is not an appropriate method. The machinability of CFRP was found to be highly influenced by the presence of residual porosity in the composite laminate. Hence, the benefit in lifetime of the diamond coating can only be utilized in machining of high quality laminates.